PEMAKAIAN BAHASA SHORT MESSAGE SERVICE (SMS) DALAM RUBRIK PEMBACA PADA SURAT KABAR BERBAHASA INDONESIA TERBITAN YOGYAKARTA - Atma Tri Jayanti; Basuki Basuki (Universitas Sarjanawiyata Tamansiswa, 2014)
The aims of this study are (1) to describe the forms of language of SMS in reader column in Indonesian newspaper, Yogyakarta edition, and (2) to describe the contents of discourse of SMS in reader column in Indonesian newspaper, Yogyakarta edition. The results of this study are 1) the forms of SMS language, and 2) discourse of SMS. The forms of SMS language included: a) the use of formal style, b) the use of informal style, and c) the use of abbreviation. The use of formal style is in the form of words, phrases, and clauses. The use of informal style included: 1) code mixing and 2) code switching. Code mixing included a) code mixing of word, b) code mixing of repeated word, c) code mixing of idiom, d) code mixing of acronym, and e) code mixing of phrase. The use of abbreviation style included 1) abbreviation, 2) fragment, 3) acronym, 4) contraction, 5) replacement of repeated word by number, 6) replacement of repeat word by punctuation mark, and 7) omission of one of the letters. The contents of SMS included: a) opinion, b) critic, c) demand, d) hope, e) advice, f) prohibition, and g) ngelulu.